Tempo de (re)criação: uma análise da relação tempo/trabalho através dos discursos de um grupo de artesãos de Juazeiro do Norte-CE - Araújo, Verônica Siqueira (2014)
This work reflects fundamentally on two categories, namely, time and craftwork. Throughout its development, the notion of craftwork is discussed through its articulation with the ideas of work and art. In this sense, the time element was introduced as a reference from which the craft activity is analyzed. To do so, it performs a brief summary on the distinct conceptions of the concept of time along history (step that fulfills the role of evidencing the non-natural disposition of the concerned category), and afterwards, it discusses the role of time in creational process. Having accomplished the dialogue between the guiding theories of this study, this work follows the presentation of the empirical research. Settled in studies of qualitative basis, the research intends to hear what a group of artisans from the city of Juazeiro do Norte – CE has to say about their activities. The responses of the artisans are analyzed through a Sociological Analysis of Speech and an ethnomethodological approach. We conclude emphasizing the existence, in our society, of a great imbalance concerning time experience and assigned value of craftwork. We suggest, thereafter, a reflection able of thinking about our social organization under different parameters than what prevails today.